2020
DOI: 10.3390/app10165581
|View full text |Cite
|
Sign up to set email alerts
|

Eucalyptus globulus Essential Oil as a Natural Food Preservative: Antioxidant, Antibacterial and Antifungal Properties In Vitro and in a Real Food Matrix (Orangina Fruit Juice)

Abstract: The potential application of Eucalyptus globulus essential oil (EGEO) as a natural beverage preservative is described in this research. The chemical composition of EGEO was determined using gas chromatography analyses and revealed that the major constituent is 1,8-cineole (94.03% ± 0.23%). The in vitro antioxidant property of EGEO was assessed using different tests. Percentage inhibitions of EGEO were dose-dependent. In addition, EGEO had a better metal ion chelating effect with an IC50 value of 8.43 ± 0.03 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 51 publications
(91 reference statements)
2
16
0
5
Order By: Relevance
“…In particular, numerous essential oils such as winter savoury, peppermint, oregano, wintergreen and eucalypt, as well as many of their principal components (carvacrol, limonene, etc.) have already exhibited attractive and useful antimicrobial, herbicidal and antioxidant activities for the agri-food industry [ 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. These data favour their potential use as natural preservatives to prevent the crop and food spoilage and extend the shelf-life, as well as weed control without significantly affecting the harvests.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, numerous essential oils such as winter savoury, peppermint, oregano, wintergreen and eucalypt, as well as many of their principal components (carvacrol, limonene, etc.) have already exhibited attractive and useful antimicrobial, herbicidal and antioxidant activities for the agri-food industry [ 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. These data favour their potential use as natural preservatives to prevent the crop and food spoilage and extend the shelf-life, as well as weed control without significantly affecting the harvests.…”
Section: Introductionmentioning
confidence: 99%
“… ( Pandey, Sonker, & Singh, 2016 ) Orangina fruit juice Eucalyptus globulus essential oil 1,8-cineole (94.03%), α-pinene (2.93%), γ-terpinene (1.93%), α-phellandrene (0.59%), β-pinene (0.20%), myrcene (0.19%) EGEO (0.8 to 4 μl/ml) was effective and potent to reduce S. cerevisiae growth in the fruit juice of Orangina. ( Boukhatem et al, 2020 ) Pineapple juice Cymbopogon citratus D.C. Stapf. essential oil (CCEO) Geraniol (46.16%), neral (31.74%), geranyl-acetate (4.34%), caryophyllene (2.02%), 6-methyl-5-hepten-2-ona (1.77%), dipentyl-ketone (1.06%), linalool (1.03%) The incorporation of CCEO in pineapple juice at all tested concentrations (5, 2.5, and 1.25 μl/ml) caused a decrease in viable counts of E. coli, L. monocytogenes, and Salmonella enterica .…”
Section: Potential and Limitation Application Of Eo As Natural Food P...mentioning
confidence: 99%
“…They found that 10% of crude and commercial clove EOs could be effective to decrease contamination and growth of L. monocytogenes . Furthermore, recent findings indicated that Eucalyptus globulus EO could reduce S. cerevisiae growth in the Orangina fruit juice ( Boukhatem, Boumaiza, Nada, Rajabi, & Mousa, 2020 ).…”
Section: Potential and Limitation Application Of Eo As Natural Food P...mentioning
confidence: 99%
“…Major substances of Eucalyptus EOs are 1,8-cineole and α-pinene (Sebei et al, 2015) or 1,8-cineole and linalool (Boukhatem et al, 2020). Essential oil of Allium sativum Linnaeus, 1793 includes organic molecules that contain sulphur, mainly diallyl disulfide, allyl propyl disulfide, allyl sulfoxide, and allicin.…”
Section: Introductionmentioning
confidence: 99%